Increased seedlings per hill compensates yield loss due to zero tillage in machine‐transplanted fragrant rice. Issue 5 (6th August 2020) - He, Longxin; Ashraf, Umair; Du, Bin; Lai, Rifang; Luo, Haowen; Abrar, Muhammad; Tang, Xiangru
Abstract: Zero tillage is a soil conservation technique. However, reduction in grain yield might be caused without the effects caused by tillage at the beginning of planting. Present study was conducted in order to test the hypothesis that increased seedlings number per hill could compensate for yield decrement under zero tillage. A two‐year field experiment was conducted between 2018 and 2019 with two fragrant rice cultivars and three treatments: convention tillage with normal seedlings number per hill (CTNS); zero tillage with normal seedlings number per hill (ZTNS) and zero tillage with high seedlings number per hill (ZTHS). The results showed that lower leaf area index, dry matter accumulation, accumulation of nitrogen, phosphorus and potassium were observed in ZTNS treatment than CTNS treatment. Compared with CTNS treatment, ZTNS treatment significantly decreased the grain yield by 11.80‐26.65%. However, the differences between ZTHS and CTNS for yield attributes (effective panicle number, grain number per panicle, seed‐setting rate and 1000‐grain weight) and grain yield were generally small during both seasons and at both sites for both cultivars. Therefore, our study indicates that increasing seedlings number per hill could be an effective strategy to compensate the potential negative effects on yield formation and grain yield of fragrant rice under zero tillage.